Vascular Tissue Engineering: Polymers and Methodologies for Small Caliber Vascular Grafts - Leal, Bruna B. J.; Wakabayashi, Naohiro; Oyama, Kyohei; Kamiya, Hiroyuki; Braghirolli, Daikelly I.; Pranke, Patricia (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease is the most common cause of death in the world. In severe cases, replacement or revascularization using vascular grafts are the treatment options. While several synthetic vascular grafts are clinically used with common approval for medium to large-caliber vessels, autologous vascular grafts are the only options clinically approved for small-caliber revascularizations. Autologous grafts have, however, some limitations in quantity and quality, and cause an invasiveness to patients when harvested. Therefore, the development of small-caliber synthetic vascular grafts (<5 mm) has been urged. Since small-caliber synthetic grafts made from the same materials as middle and large-caliber grafts have poor patency rates due to thrombus formation and intimal hyperplasia within the graft, newly innovative methodologies with vascular tissue engineering such as electrospinning, decellularization, lyophilization, and 3D printing, and novel polymers have been developed. This review article represents topics on the methodologies used in the development of scaffold-based vascular grafts and the polymers used in vitro and in vivo.